Roles and Impact of Strategic Human Resources Management to Firm Performance : Case Study on a Gas and Utilities Company in Malaysia - Lee, Chang Quan (2015)
This management project research work takes a case study approach to a local gas and utilities company in Malaysia in examining the strategic link between human resource architecture and business strategy. It then provides an insight to the link between strategic human resource management implementation and firm performance. By implementing strategic human resource management practices in area of selection, development, appraisal and reward, improved firm performance is expected. Strategic role of human resource management would be explored in providing a sustained competitive advantage to the firm which lead to positive impact on firm performance. The ‘how’ part of strategic human resource management would be examined to identify the key success factors for effective implementation.